(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aims to analyze the value system embedded in digital advertisements on TikTok and to examine its patterns and relationships with creative features—namely influencer presence, music, visual style, and product type—in light of the Cultivation Theory and Social Learning Theory. The objective is to determine the nature of the values conveyed by these advertisements and their alignment with the cultural identity of Saudi youth. A descriptive–analytical approach was employed, supported by statistical tests (χ² and Cramér’s V), through content analysis of a purposive sample of 200 advertisements representing the most prevalent categories on the platform: fashion and beauty, technology and gaming, and food and apps. The results revealed a dominance of individualistic, hedonic, consumerist, and modern values exceeding 60%, accompanied by a decline in social and cultural values. A statistically significant relationship was found between influencer presence and individualistic values (p = 0.002, V = 0.21). Significant differences also emerged between product type and value patterns (p < 0.001, V = 0.38), as well as between local and global brands (p < 0.001, V = 0.30). Music showed a positive yet non-significant tendency (p = 0.075) to enhance hedonic values. Overall, the findings indicate a trend toward value globalization and underscore an individualistic–consumerist orientation in TikTok advertising. The study introduces the concept of Interactive Value Cultivation to explain how values are reproduced within digital interactive environments.